P-proteins in Arabidopsis are heteromeric structures involved in rapid sieve tube sealing - Jekat, Stephan B.; Ernst, Antonia M.; von Bohl, Andreas; Zielonka, Sascia; Twyman, Richard M.; Noll, Gundula A.; Prüfer, Dirk (Frontiers in Plant Science, 2013)
Structural phloem proteins (P-proteins) are characteristic components of the sieve elements in all dicotyledonous and many monocotyledonous angiosperms. Tobacco P-proteins were recently confirmed to be encoded by the widespread sieve element occlusion (SEO) gene family, and tobacco SEO proteins were shown to be directly involved in sieve tube sealing thus preventing the loss of photosynthate. Analysis of the two Arabidopsis SEO proteins (AtSEOa and AtSEOb) indicated that the corresponding P-protein subunits do not act in a redundant manner. However, there are still pending questions regarding the interaction properties and specific functions of AtSEOa and AtSEOb as well as the general function of structural P-proteins in Arabidopsis. In this study, we characterized the Arabidopsis P-proteins in more detail. We used in planta bimolecular fluorescence complementation assays to confirm the predicted heteromeric interactions between AtSEOa and AtSEOb. Arabidopsis mutants depleted for one or both AtSEO proteins lacked the typical P-protein structures normally found in sieve elements, underlining the identity of AtSEO proteins as P-proteins and furthermore providing the means to determine the role of Arabidopsis P-proteins in sieve tube sealing. We therefore developed an assay based on phloem exudation. Mutants with reduced AtSEO expression levels lost twice as much photosynthate following injury as comparable wild-type plants, confirming that Arabidopsis P-proteins are indeed involved in sieve tube sealing.